OPTIMIZATION THE COMBINED INTAKE OF SUGAR-SALT-FAT USING GENETICH ALGORITHM - Marpaung, Preddy; Sitio, Arjon Samuel; Sinaga, Anita Sindar RM (Politeknik Ganesha Medan, 2020)
Salt sugar and fat intake in the human body in daily food patterns. To avoid non-communicable diseases, it is necessary to optimize food intake levels. Productive age, in this case between 15-55 years have uncontrolled eating patterns to choose fast food. If this is not monitored, it will cause various diseases. The importance of evolutionary algorithms for solving complex problems that are difficult to solve analytically can use mathematical models. The purpose of this study is to determine the composition of the ideal intake for productive generations with a minimum cost that must meet the minimum threshold for each nutritional component. Based on the mathematical model built, an analysis is carried out to find the optimal solution. Optimization is an effort or activity to get the best results with the given requirements. There are 5 main components in the Genetic Algorithm, namely Fitness, Value, Selection, Crossover, and Mutation. The results showed optimization of the intake of selected chromosomes as the best results, obtained on chromosome offSpring: 10, Fitness value: 12737.34.